Wobby #22 : Outbreak : Volume 6. - Schalk, Marjolein; Cartwright, Andrew; de Leijer, Boris; Smout, Bart ([s.l.] : Wobby-club)
Contributors Wobby#22 : Nel Aerts (BE) ; Martien Bos (NL) ; Burnbjoern (AT) ; Joakim Drescher (DK) ; Loulou João (BE) ; Delphine Lecompte (BE) ; Jeroen de Lijer (NL) ; Ulrika Netzler (SE) ; Bobbi Oskam (NL) ; Joost Pollman (NL) ; Rachel O'Regan (Ie) ; Marjolein Schalk (NL) ; João Sobral (Pt/UK) ; Erik Svetoft (SE) ; Indre Svirplyte (LG/BE) ; S.L. Trumpstein (NL) ; Nina van de Ven (NL) ; Judith Weber (DE) ; Noa Zuidervaart (NL) - Art Direction & Risoprinting : Marjolein Schalk & Bobbi Oskam.
boek